2010
DOI: 10.1038/hr.2010.226
|View full text |Cite|
|
Sign up to set email alerts
|

Ambulatory blood pressure profile in hypertensive patients with β-thalassemia minor

Abstract: b-thalassemia trait (b-TT) is a common genetic disorder in Mediterranean countries, including Greece. Previous studies have shown the protective effect of b-TT against myocardial infarction. However, the ambulatory blood pressure (BP) profile of such patients has not yet been investigated. Thus, the purpose of the present study was to investigate the ambulatory BP monitoring (ABPM) profile of hypertensives with b-TT, in comparison with all-cause anemic and non-anemic essential hypertensive patients. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…[ 12 , 13 , 14 ]. Further reinforcing this link, in a study by Vyssoulis et al [ 15 ], hypertensive patients with βTM presented a better 24-hour blood pressure profile compared to patients without βTM.…”
Section: Discussionmentioning
confidence: 76%
“…[ 12 , 13 , 14 ]. Further reinforcing this link, in a study by Vyssoulis et al [ 15 ], hypertensive patients with βTM presented a better 24-hour blood pressure profile compared to patients without βTM.…”
Section: Discussionmentioning
confidence: 76%
“…Thalassemia major patients with diabetes mellitus had a higher risk of cardiac complications, including heart failure, hyperkinetic arrhythmias, and myocardial fibrosis [ 93 ]. A protective effect of beta-thalassemia against myocardial infarction was demonstrated in thalassemia minor due to a favorable lipidemic profile, a better cardiovascular risk factor, and 24 h blood pressure profile, compared with anemic and nonanemic hypertensives [ 94 , 95 ].…”
Section: Cardiovascular Consequences Of Hereditary Forms Of Anemiamentioning
confidence: 99%
“…Besides, decreased blood viscosity due to the decreased hematocrit level can improve circulation [12,13]. In accordance with this link, hypertensive patients with BTM presented with a better 24-h blood pressure profile compared to patients without BTM [14]. Baserga et al [15] reported a lower incidence of hypertension in subjects with BTM.…”
Section: Discussionmentioning
confidence: 52%